Fall and Revival of City Centre Retailing: Planning an Urban Function in Leicester, Britain - Nagy, Erika (Discussion Papers, 1999)
The purpose of the present study is to analyse the changing structure and spatial forms of retailing activities in the city centre after the World War II. To reveal economic and social changes behind the declining business of small corner shops and rise of large shopping malls, the study was extended to three topics: • economic, social and environmental problems of city centres; • structural and organisational transformation of the retail sector and the spatial consequences of that; • central and local governmental attitudes towards the processes mentioned above in terms of town planning and retailing. The topics are discussed in the main sections of the paper, with strong emphasis on the changes of retailing in the city centre. To represent the local effects of the nation-wide structural changes, retailing and city centre development policies, the author studied the example of Leceister in details. To find a working definition for the area, the author used the approach of town planners. The paper focuses on the period between the early 1950s and the mid-1990s, a period when the scale and structure of the consumption and organisation of the retailing sector was changing considerably leading to the emergence of new spatial forms of retailing, such as out-of-town shopping malls, hypermarkets and shopping precincts. The periodisation corresponds with local and central governmental policies that followed the fluctuation of the demand and retail investments. The changes in the retail sector were determined by widespread processes such as the structural and organisational changes of the retail sector, deconcentration of the urban population and transformation of shopping behaviour.